Politeness and Camaraderie: How Types of Form Matter in Indonesian Context - . Jumanto (Bandar Lampung University (UBL), 2014)
This article is about politeness and camaraderie through pragmatic viewpoints within Indonesian context. A language, the writer argues, should be directed to politeness (distant language) and camaraderie (close language), the two varieties of language use in some diglossic speech situation. The writer’s arguments are, among others, that distant language is formal, indirect, and non-literal, and that close language is informal, direct, and literal. Distant language is spoken to hearers with power factor, while close language is spoken to hearers with solidarity factor. Ignorance or incompetence of this may cause impoliteness, i.e. rude situations or awkward situations in interpersonal interactions. This tendency elaborates pragmatic viewpointsfrom Goffman’spositive and negative face [1], Brown and Levinson’s positive and negative politeness strategies[2], Renkema’s solidarity and respect politeness[3],Jumanto’s friendship and politeness[4],[5], and types of hearer elaborated by Brown and Gilman[6]and advocated by Jumanto[5]. Examples in the Indonesian language, based on a simple emic research, are given to support the everyday-use-of-Indonesian-language arguments.